1995
DOI: 10.1074/jbc.270.28.16495
|View full text |Cite
|
Sign up to set email alerts
|

Gβγ Subunits Mediate Mitogen-activated Protein Kinase Activation by the Tyrosine Kinase Insulin-like Growth Factor 1 Receptor

Abstract: The receptors for insulin-like growth factor 1 (IGF1) and insulin are related heterotetrameric proteins which, like the epidermal growth factor (EGF) receptor, possess intrinsic ligand-stimulated tyrosine protein kinase activity. In Rat 1 fibroblasts, stimulation of mitogen-activated protein (MAP) kinase via the IGF1 receptor and the Gi-coupled receptor for lysophosphatidic acid (LPA), but not via the EGF receptor, is sensitive both to pertussis toxin treatment and to cellular expression of a specific G beta g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

13
154
0

Year Published

1997
1997
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 199 publications
(167 citation statements)
references
References 39 publications
13
154
0
Order By: Relevance
“…The involvement of G i in regulating growth-factor-receptor signalling is supported by studies from Luttrell and colleagues [8]. These authors showed that PTX and an inhibitor of G i βγ-mediated signalling (C-terminal domain of β-adrenergic receptor kinase) blocked the activation of p42\p44 MAPK by insulin and insulin-like-growth-factor-1 receptors in rat 1A fibroblasts.…”
Section: Role Of C-srcmentioning
confidence: 88%
See 1 more Smart Citation
“…The involvement of G i in regulating growth-factor-receptor signalling is supported by studies from Luttrell and colleagues [8]. These authors showed that PTX and an inhibitor of G i βγ-mediated signalling (C-terminal domain of β-adrenergic receptor kinase) blocked the activation of p42\p44 MAPK by insulin and insulin-like-growth-factor-1 receptors in rat 1A fibroblasts.…”
Section: Role Of C-srcmentioning
confidence: 88%
“…There are two exceptions, namely insulin and insulin-like-growth-factor-1 receptor, which stimulate p42\ p44 MAPK activation in a pertussis toxin (PTX)-sensitive manner in fibroblasts [8]. In contrast, there is a growing body of evidence to suggest that G i -coupled receptor agonists can stimulate growth-factor-receptor transactivation [9][10][11][12].…”
Section: Introductionmentioning
confidence: 99%
“…The IGF-IR activates heterotetrameric G proteins in certain cell types. It has been reported that the βγ subunits of the Gi class of G proteins can mediate IGF-I-induced activation of MAP kinase (Luttrell et al, 1995). In addition, it has been demonstrated that the IGF-IR forms a complex with the Gα subunit of Gi proteins (Dalle et al, 2001).…”
Section: Receptor Cross-talkmentioning
confidence: 99%
“…To verify that this dose of PTX will inactivate G i , we determined whether PTX could block LPA signaling in hIRcB cells. LPA has been shown to signal through the G i heterotrimeric protein leading to G␤␥-mediated activation of MAPK (30). Pretreatment of cells with PTX reduced ERK activation in response to 10 M LPA by immunoblotting, whereas activation by insulin was unaffected ( Fig.…”
Section: Gnrh-mediated Signaling Is Pertussis Toxin-insensitive In L␤t2mentioning
confidence: 99%
“…Expression of Fusion Proteins-The ␤ARK-CT fusion protein was purified as a GST fusion protein as described previously (30). For the TAT fusion peptides, oligonucleotides encoding the G q -CT (QLNLKEYNLV), G s -CT (RMHLRQYELL), or PLC␤2 (NRSYVISSFTELKAYDLLSK) peptides were cloned into expression vector pTAT-HA (31).…”
Section: Methodsmentioning
confidence: 99%